Bile acid dysmetabolism in the gut‐microbiota‐liver axis under hepatitis C virus infection. (5th September 2021) - Inoue, Takako; Funatsu, Yui; Ohnishi, Masaya; Isogawa, Masanori; Kawashima, Keigo; Tanaka, Masaru; Moriya, Kei; Kawaratani, Hideto; Momoda, Rie; Iio, Etsuko; Nakagawa, Hidewaki; Suzuki, Yutaka; et al.
Abstract: Background & Aims: We recently analysed and reported the features of the micro biome under hepatitis C virus (HCV) infection, but the effect of HCV infection on bile acid (BA) metabolism in the gut‐liver axis remains poorly understood. The aim of this study was to clarify the characteristics of the gut‐liver axis in HCV‐infected patients. Methods: The faecal BAs composition and gut microbiota from 100 chronic hepatitis C (CHC) patients were compared with those from 23 healthy individuals. For transcriptional analysis of the liver, 22 mild CHC (fibrosis stages [F] 0‐2) and 42 advanced CHC (F3‐4) cases were compared with 12 healthy individuals. The findings were confirmed using chimeric mice with human hepatocytes infected with HCV HCR6. Results: Chronic hepatitis C patients, even at earlier disease stages, showed BA profiles distinct from healthy individuals, in which faecal deoxycholic acid (DCA) was significantly reduced and lithocholic acid or ursodeoxycholic acid became dominant. The decrease in faecal DCA was correlated with reduction in commensal Clostridiales and increase in oral Lactobacillales . Impaired biosynthesis of cholic acid (CA) was observed as a reduction in the transcription level of cytochrome P450 8B1 (CYP8B1), a key enzyme in CA biosynthesis. The reductions in faecal DCA and liver CYP8B1 were also observed in HCV‐infected chimeric mice. Conclusions: Chronic hepatitis C alters the intestinal BA profile, in association with the imbalance of BA biosynthesis, which differs from the pattern in NAFLD. These imbalances appear to drive disease progression through the gut‐microbiome‐liver axis.